Optimal configuration and pressure levels of electrolyzer plants in context of power-to-gas applications. (1st April 2016) - Bensmann, B.; Hanke-Rauschenbach, R.; Müller-Syring, G.; Henel, M.; Sundmacher, K.
Highlights: Identification of best pressure profiles for H2 production, compression and drying. High hydrogen production pressures strongly reduce effort for product drying. Electrolysis with subsequent compression is favorable for high delivery pressures. Hydrogen crossover strongly reduces efficiency for medium electrolyzer pressures. Drying should happen at the end of the process, after mechanical compression. Abstract: Typical power-to-gas plants mainly consist of a water electrolyzer, a mechanical compressor, an active cooler and a dryer. The best sequence of the single components as well as the pressure levels throughout the process are ambiguous. They depend on the hydrogen delivery pressure and the humidity requirements of the final product. The present analysis is based on a uniform technology independent model framework of the single process units. It allows for the calculation of the overall energy demand, independent of the requirements on hydrogen pressure and water content. In the present contribution two main superordinate configurations, which differ in the sequence of mechanical compressor and dryer, are compared and the best pressure profile throughout the process is determined. The analysis exemplarily focuses on hydrogen delivery pressures between 1 and 100 bar and an aimed maximal water content of 5 μ mol / mol, as required e.g. for automotive applications. The results show that the energy demand for drying dominates the total energy balance at low delivery pressure. Higher electrolyzer pressures increase the losses due to hydrogen crossover. A mechanical compression prior to drying can be used to reduce the overall energy demand of the process. The electrolyzer pressure can be kept below 20 bar, which reduces hydrogen crossover and besides enables anyhow efficient drying at high pressures.